Well first you change x - 2y = .9 to x = .9 + 2y, by adding y from both sides of the equation.
Then, you substitute x=.9 + 27 into 4x - 3y = 13.1 to get 4(.9 + 2y)- 3y= 13.1. Use the distrubutive property and you get 4 * .9 = 3.6 and 4 * 2y = 8y.
Now you have 3.6 + 8y - 3y = 13.1. Simplify to get 3.6 + 5y = 13.1, since 8y - 3y = 5y.
So you subtract 3.6 from both sides to get 5y = 9.5. Divide this by -9 on both sides to get y = 1.9
Plug this in to one of the equations: x - 2y = .9 to get x - 2(1.9) = .9.
You get x - 3.8 = .9. Add 3.8 to both sides to get x=4.7.
The answer is (4.7 , 1.9)
Answer this Question
Algebra 1 - bobpursey, In this problem you helped me with earlier: Solve using ...
Substitution Method-Plz help - Use the Substitution method to solve the system ...
Algebra Help!! - solve using the substitution method. y= 5 - 3x 4x + y= 7
Algebra - Solve using substitution method 3x+8y=20 x=24-7y
Algebra - 4x+y=42 6x-5y=50 Solve using the substitution method.
Algebra - Solve using the substitution method. 0.3x+0.2y=5,0.5x+0.4y=11
algebra - Solve using the substitution method 6x-3y=18, 6x+3y=-12
algebra - using the substitution method how do you solve y=-1/3x y+2x=5
Algebra - solve using substitution method 3x-5y=61 3x-y=17
algebra - x+3y=-10 7x-5y=34 solve using substitution method